Typhaneoside-Tetrahedral Framework Nucleic Acids System: Mitochondrial Recovery and Antioxidation for Acute Kidney Injury treatment - Yan, Ran; Cui, Weitong; Ma, Wenjuan; Li, Jiajie; Liu, Zhiqiang; Lin, Yunfeng (ACS nano, 2023)
Acute kidney injury (AKI) is not only a worldwide problem with a cruel hospital mortality rate but also an independent risk factor for chronic kidney disease and a promoting factor for its progression. Despite supportive therapeutic measures, there is no effective treatment for AKI. This study employs tetrahedral framework nucleic acid (tFNA) as a vehicle and combines typhaneoside (Typ) to develop the tFNA-Typ complex (TTC) for treating AKI. With the precise targeting ability on mitochondria and renal tubule, increased antiapoptotic and antioxidative effect, and promoted mitochondria and kidney function restoration, the TTC represents a promising nanomedicine for AKI treatment. Overall, this study has developed a dual-targeted nanoparticle with enhanced therapeutic effects on AKI and could have critical clinical applications in the future.